2014
DOI: 10.1007/s13139-014-0303-3
|View full text |Cite
|
Sign up to set email alerts
|

Value of 18F-FDG PET/CT in the Detection of Ovarian Malignancy

Abstract: Purpose Ovarian cancer is a leading cause of gynecologic malignancy. As symptoms of ovarian cancer are nonspecific, only 20 % of ovarian cancers are diagnosed while they are still limited to the ovaries. Thus, early and accurate detection of disease is important for an improved prognosis. For the accurate and effective diagnosis of ovarian malignancy on 18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…SUV is the radioactivity per unit volume (as a numerator) divided by the injected radioactivity per unit weight (as a denominator). [ 20 , 21 ] SUVmean represents the average radioactivity in the thyroid, and SUVmax reflects the maximum radioactivity in a single voxel within the thyroid. In the present study, SUVmean and SUVmax showed comparable accuracy with the %thyroid uptake in terms of differentiation of thyroid diseases (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SUV is the radioactivity per unit volume (as a numerator) divided by the injected radioactivity per unit weight (as a denominator). [ 20 , 21 ] SUVmean represents the average radioactivity in the thyroid, and SUVmax reflects the maximum radioactivity in a single voxel within the thyroid. In the present study, SUVmean and SUVmax showed comparable accuracy with the %thyroid uptake in terms of differentiation of thyroid diseases (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These studies included 604 cases. Four of these studies were excluded as we were unable to create two-by-two tables[ 2 20 21 22 ] and one was excluded as it involved staging of mixed gynecological malignancies. [ 8 ] Thus, we included 8 studies and total of 380 patients that were focused on staging OC.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Many studies have been conducted to optimize the effective diagnosis and treatment of ovarian cancer. In a comparison study of 51 patients with peritoneal lesions arising from ovarian cancer, it was demonstrated that the obtained visual results of [ 18 F]FDG PET/CT in association with other semi-quantitative parameters were effective in the detection of ovarian cancer [ 56 ]. This result was based on the observed differentiation potency of [ 18 F]FDG PET/CT in malignant and benign lesions [ 56 ].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In a comparison study of 51 patients with peritoneal lesions arising from ovarian cancer, it was demonstrated that the obtained visual results of [ 18 F]FDG PET/CT in association with other semi-quantitative parameters were effective in the detection of ovarian cancer [ 56 ]. This result was based on the observed differentiation potency of [ 18 F]FDG PET/CT in malignant and benign lesions [ 56 ]. In another study, results showed that CA125 acted as a sensitive tumor marker of recurrent ovarian cancer in 175 patients with recurrent refractory ovarian cancer and increased carcinoma antigen 125 (CA125).…”
Section: Ovarian Cancermentioning
confidence: 99%